Analysis of cosmic ray variations observed by the CARPET in association with solar flares in 2011-2012 - Makhmutov, V. (2013)
The CARPET cosmic ray detector was installed on April 2006 at CASLEO (Complejo Astronmico El Leoncito) at the Argentinean Andes (31.8S, 69.3W, 2550 m, Rc=9.65 GV). This instrument was developed within an international cooperation between the Lebedev Physical Institute RAS (LPI; Russia), the Centro de Radio Astronomia e Astrofsica Mackenzie (CRAAM; Brazil) and the Complejo Astronmico el Leoncito (CASLEO; Argentina). In this paper we present results of analysis of cosmic ray variations recorded by the CARPET during increased solar flare activity in 2011-2012. Available solar and interplanetary medium observational data obtained onboard GOES, FERMI, ISS, as well as cosmic ray measurements by ground-based neutron monitor network were also used in the present analysis.